The cardioprotective mechanisms of draconis sanguis: An integrated network pharmacology, bioinformatics, and experimental validation study - Keyan Wang; Rongxin Zhu; Junjun Li; Binhua Yuan; Xiang Li; Yunlin Li; Mingyue Huang; Fangfang Rui; Chun Li; Wei Wang (Journal of Traditional Chinese Medical Sciences)
Objective: To investigate the potential targets and mechanisms of Draconis Sanguis (DS), a valuable traditional Chinese medicine derived from the resin of the palm tree Daemonorops draco Bl (D. Sanguis, Xue Jie), in the treatment of myocardial infarction (MI). Methods: We explored the potential mechanisms of DS in the treatment of MI using network pharmacology, bioinformatic techniques, and transcriptomic analysis, followed by validation through in vivo and in vitro experiments. Results: Network pharmacology and bioinformatic analyses identified five genes (Fpr1, Glul, Mme, Mmp9, and Pla2g7) as potential targets for MI treatment. Moreover, DS significantly ameliorated cardiac function, inflammatory responses, and MI-induced myocardial fibrosis in vivo. Transcriptomic and bioinformatic analyses identified Pla2g7 as the most critical target in the DS treatment of MI. Molecular docking revealed that the key active ingredient in DS has a strong affinity for this gene. Furthermore, DS reduced the expression of Pla2g7 (P = .0009), NLRP3 (P = .003), interleukin-18 (P < .001), and interleukin-1β (P = .004) mRNAs in vivo. Conclusions: The results indicate that DS can downregulate the expression of Pla2g7 and reduce the inflammatory response. This demonstrates the potential therapeutic target of DS and the mechanism underlying its cardioprotective effects.